Gross Domestic Product and Economic Value of Water Resources of River Basins in Thailand - ชื่นชุ่ม, ภวิสร (Srinakharinwirot University Engineering Journal, 2020)
Water resources are mainly natural resources for the economic development of each country in the world. In recent, the climate change has affected water resources in the productive process of every economic sector. It is imperative to have a consideration for water allocation in economic efficiency. This study aims to calculate the gross domestic product (GDP) and water demand in each sub-district (tambon) and assess the economic value of water (GDP/cu.m.) of 25 basins in Thailand. GDP and water demand were considered from the main economic sectors of Thailand such as agriculture, manufacturing, and service. They were estimated using the available secondary database from government’s agencies. The results showed the GDP of basins, which found that the Chao Phraya River Basin is the maximum GDP, but it consumed only the moderate water. In addition, the economic value of water in the manufacturing sector is the highest values in generating the GDP. This study can recommend the policymakers for the design of economic and environmental policies in driving Thailand’s economy.